2006
DOI: 10.1086/500357
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Star Formation in L1551

Abstract: The L1551 molecular cloud, unlike most of the Taurus Molecular Complex, is undergoing a long and sustained period of relatively high efficiency star formation. It contains two small clusters of Class 0 and I protostars, as well as a halo of Council of Canada's Herzberg Institute of Astrophysics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 58 publications
4
73
0
Order By: Relevance
“…Since low mass protostars evolve approximately at the same rate to the main sequence, the different evolutionary stages found in I00213 suggest that stars in this region are not forming simultaneously but continuously. Also, there may be different generations due to different timescales of core collapse, as has been found in other low mass star-forming regions (e.g., L1551: Moriarty-Schieven et al 2006), indicating that the formation of different stars is not simultaneous but sequential in time, possibly triggered by the interaction of the molecular outflow with a dense core in its surroundings (Yokogawa et al 2003;Shimajiri et al 2008). Therefore, the initial assumption that star formation occurs in an isolated mode may not be appropriate to describe the I00213 region when the region is studied with high angular resolution.…”
Section: Discussionmentioning
confidence: 89%
“…Since low mass protostars evolve approximately at the same rate to the main sequence, the different evolutionary stages found in I00213 suggest that stars in this region are not forming simultaneously but continuously. Also, there may be different generations due to different timescales of core collapse, as has been found in other low mass star-forming regions (e.g., L1551: Moriarty-Schieven et al 2006), indicating that the formation of different stars is not simultaneous but sequential in time, possibly triggered by the interaction of the molecular outflow with a dense core in its surroundings (Yokogawa et al 2003;Shimajiri et al 2008). Therefore, the initial assumption that star formation occurs in an isolated mode may not be appropriate to describe the I00213 region when the region is studied with high angular resolution.…”
Section: Discussionmentioning
confidence: 89%
“…The SED in the MIR has been measured with ISOCAM/ISO (Stapelfeldt & Moneti 1999;Brandner et al 2000) and refined substantially by observations with IRS on the Spitzer Space Telescope (SST, Furlan et al 2008). Mapping of continuum fluxes at (sub)mm-wavelengths, observations of rotational transitions of CO isotopes and HCO + , and high-resolution imaging with interferometers have provided valuable insights revealing the dynamics of the gaseous component, its temperature distribution and the very low spectral index β mm ∼ 0.4 of the dust (Reipurth et al 1993;Padgett et al 2001;Moriarty-Schieven et al 2006;P06;G08). We will present the most prominent observations used for this study in the following paragraphs, the photometric data is shown in Fig.…”
Section: Observationsmentioning
confidence: 99%
“…This strange behaviour was the main reason for several authors to consider this flow as an intersection of two jets: one from HL Tau and another from the hypothetical source VLA 1 (Mundt et al 1987). But sub-millimeter (Moriarty-Schieven et al 2006) and various infrared observations of this region did not confirm the existence of any source in the position of the VLA 1. Presently the HH 151 jet is considered as a single flow from HL Tau itself.…”
Section: Introductionmentioning
confidence: 97%